The variation in transparency of amniotic membrane used in ocular surface regeneration. Issue 8 (19th March 2009) - Connon, C J; Doutch, J; Chen, B; Hopkinson, A; Mehta, J S; Nakamura, T; Kinoshita, S; Meek, K M
Abstract : Background/aims: Scant consideration has been given to the variation in structure of the human amniotic membrane (AM) at source or to the significance such differences might have on its clinical transparency. Therefore, we applied our experience of quantifying corneal transparency to AM. Methods: Following elective caesarean, AM from areas of the fetal sac distal and proximal (ie, adjacent) to the placenta was compared with freeze-dried AM. The transmission of light through the AM samples was quantified spectrophotometrically; also, tissue thickness was measured by light microscopy and refractive index by refractometry. Results: Freeze-dried and freeze-thawed AM samples distal and proximal to the placenta differed significantly in thickness, percentage transmission of visible light and refractive index. The thinnest tissue (freeze-dried AM) had the highest transmission spectra. The thickest tissue (freeze-thawed AM proximal to the placenta) had the highest refractive index. Using the direct summation of fields method to predict transparency from an equivalent thickness of corneal tissue, AM was found to be up to 85% as transparent as human cornea. Conclusion: When preparing AM for ocular surface reconstruction within the visual field, consideration should be given to its original location from within the fetal sac and its method of preservation, as either can influence corneal transparency.